A Teacher’s Perspective on the Techniques of Teaching Speaking to Young EFL Learners - Pertiwi, Puteri; Hapsari, Astri (PrimaryEdu : Journal of Primary Education, 2022)
Teching EFL speaking to young learners need a wide range of techniques which makes them willing to learn and engage in their learning. The aim of this study is to investigatean English teacher’s perspective in the techniques of teaching speaking for young EFL learners within the context of an intenational primary school. A descriptive qualitative method was employed by using interview questions as the instrument for data elicitation. The participant was a female English teacher in an international primary school at grade 1. The findings revealed that the use of various teaching techniques in speaking can help the teacher to gain student’s motivation and create student’s new learning experience. The technique of teaching speaking to young EFL learners used by the teacher  which were identified is a combination of the police of English and getting good stars as a reward repetition drill technique, and translation which were perceived by the teacher scaffold young learners’ learning process in speaking. It is recommended that the teacher’s best practice in implementing a wide range techniques should be sustained in supporting young learners learn how to speak in English